Efektivitas LKPD Stoikiometri Berbasis Project-Based Learning dengan Memanfaatkan Limbah Organik terhadap Hasil Belajar Peserta Didik Fase E SMA/MA - Harefa, Mila Juliana; Suryani, Okta (TSAQOFAH, 2025)
The low learning outcomes of students on stoichiometry material highlight the need for the development of contextual and applicative learning media. This study aims to determine the effectiveness of using student worksheets (Lembar Kerja Peserta Didik, LKPD) based on project-based learning that incorporates the use of organic waste in improving the learning outcomes of phase E students at the senior high school (SMA/MA) level. The research design employed a quasi-experimental approach using a pretest-posttest model with two groups: an experimental class and a control class. The instruments used were pretest and posttest assessments to measure learning improvement. The t-test results showed a value of 5.17 > 2.01, indicating a significant difference between the experimental and control groups. Thus, the use of project-based LKPD integrating environmental issues through organic waste utilization was proven effective in enhancing student learning outcomes. The study concludes that a contextual, project-based learning approach can serve as an innovative alternative in teaching chemistry, particularly in stoichiometry. The implications of this research encourage educators to design LKPDs that are not only theoretical but also practical and relevant to everyday life.